pengulangan tindak pidana (residivis), atau perbuatan yang menimbulkan keresahan di masyarakat. Sebaliknya, keadaan yang meringankan dapat berupa sikap sopan terdakwa selama persidangan, pengakuan dan penyesalan atas perbuatannya, belum pernah dihukum, ad - dikir dakhi (JURNAL PANAH KEADILAN, 2026)
An acquittal in an abortion case is an interesting court decision to study because it concerns aspects of protecting the rights to life, health, and legal certainty in the criminal justice system in Indonesia. This study aims to analyze the basis of the judge's legal considerations in issuing an acquittal in an abortion crime case and to examine its compliance with the provisions of criminal law and criminal procedure law applicable in Indonesia. Abortion comes from the word Abortus ( Latin ) which means premature miscarriage. The act of abortion is no longer a public secret and is not something taboo. The crime of abortion is... is often carried out by teenagers and adult women, both married and unmarried. The crime of abortion must be accountable according to the consequences of their actions. This research uses a normative legal research method with a statutory approach, a case approach, and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials which are analyzed qualitatively. The results of the study show that an acquittal is issued if the elements of the crime charged by the public prosecutor are not legally and convincingly proven based on the evidence presented at trial. The judge's considerations in issuing an acquittal verdict are based on the legal facts revealed during the trial, assessment of the evidence, witness statements, expert statements, and the application of provisions of laws and regulations governing the crime of abortion and criminal procedural law. An acquittal reflects the application of the presumption of innocence, the principle of legal proof, and the independence of judges in deciding cases. Therefore, an acquittal does not necessarily indicate that the alleged act never occurred, but rather that the evidence presented at trial did not meet the legally required standard of proof.